2017
DOI: 10.1158/1078-0432.ccr-17-1397
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Molecular, and Clinical Characterization of Succinate Dehydrogenase Subunit A Variants of Unknown Significance

Abstract: Purpose Patients who inherit a pathogenic loss-of-function genetic variant involving one of the four succinate dehydrogenase (SDH) subunit genes have up to an 86% chance of developing one or more cancers by the age of 50. If tumors are identified and removed early in these high-risk patients, they have a higher potential for cure. Unfortunately, many alterations identified in these genes are variants of unknown significance (VUS), confounding the identification of high-risk patients. If we could identify miscl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…Genetic studies have indicated that the loss of function of SDH is the result of the combination of an inactivating germline mutation with a somatic loss of heterozygosity affecting the other allele. More recently, the biological effect of the R589W SDHA mutation has been assessed in tumor tissue and in a yeast model system (29,30). The R589W mutation causes pseudohypoxia and promotes cell proliferation and angiogenesis, which supports the hypothesis that SDHA may function as a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies have indicated that the loss of function of SDH is the result of the combination of an inactivating germline mutation with a somatic loss of heterozygosity affecting the other allele. More recently, the biological effect of the R589W SDHA mutation has been assessed in tumor tissue and in a yeast model system (29,30). The R589W mutation causes pseudohypoxia and promotes cell proliferation and angiogenesis, which supports the hypothesis that SDHA may function as a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from their interactions with HSP90, SDHA mutants also play a critical role in the function of the SDHA-SDHB-SDHC-SDHD complex. These loss-of-function mutations fail to consume oxygen and result in a dramatic decrease in SDHB expression, which increases succinate and reactive oxygen species (ROS) levels and ultimately triggers tumor formation (29). Interestingly, these variants had differential effects on SDHA flavination and/or protein abundance.…”
Section: Discussionmentioning
confidence: 99%
“…SDHA c.778G>A (p.Gly260Arg) was detected in a patient negative for SDHB , SDHD , VHL , and RET genes. This was a previously reported variant in paraganglioma [ 14 16 ], known to be a loss-of-function variant according to functional studies [ 15 ]. KIF1B c.2787-2A>C, a likely pathogenic variant that had not been previously reported, was detected in a patient with a bladder paraganglioma.…”
Section: Resultsmentioning
confidence: 86%
“…Among the 36 patients found to be negative for routine clinical gene testing, only two were found to be positive for likely pathogenic variants (2/36=5.6%). SDHA c.778G>A (p.Gly260Arg) was shown to be a loss-of-function variant in functional studies in a yeast strain lacking Sdh1 [ 15 ]. Pathogenic germline SDHA variants were previously identified in 7.6% of patients with PGL, with diagnosis occurring at a significantly younger age in patients carrying the SDHA variants [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our data are compatible with the idea that the elevated risk of cancer in the proband and her family may arise from the interaction of two or more rare variants. Comprehensive reviews of SDHA variants over a large disease spectrum in various databases have been published (Bannon, et al, 2017;Casey, et al, 2017;Evenepoel, et al, 2015). To date, there have been few reports of SDHA mutations in sporadic renal cancer: for example, a 17 kbp homozygous deletion leading to the loss of 9 exons of SDHA , a heterozygous germline mutation in the initiation codon (Jiang, et al, 2015), a splice site deletion (Ozluk, et al, 2015), and a combined germline/somatic biallelic loss (McEvoy, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%